Root Extract of Polygonum cuspidatum Siebold & Zucc. Ameliorates DSS-Induced Ulcerative Colitis by Affecting NF-kappaB Signaling Pathway in a Mouse Model via Synergistic Effects of Polydatin, Resveratrol, and Emodin - Liu, Baohai; Li, Shuangdi; Sui, Xiaodan; Guo, Lianyi; Liu, Xingmei; Li, Hongmei; Gao, Leming; Cai, Shusheng; Li, Yanrong; Wang, Tingting; Piao, Xuehua (Frontiers in Pharmacology, 2018)
Background: Polygonum cuspidatum Siebold & Zucc. (PCS) has antibacterial properties and may prevent Ulcerative colitis (UC) but related molecular mechanism remains unknown. NF-кB signaling pathway is associated with inflammatory responses and its inactivation may be critical for effective therapy of UC. Methods: UC mouse (C57BL/6J) model was established by using dextran sulfate sodium (DSS). The extract of PCS (PCSE) was prepared by using ethanol and its main ingredients were measured by HPLC. Thirty-two UC mice were evenly assigned into DG (received vehicle control), LG (0.1g/kg PCSE daily), MG (0.2g/kg PCSE daily) and HG (0.4 g/kg PCSE daily) groups. Meanwhile, 8 healthy mice were assigned as a control group (CG). Serum pharmacokinetics of PCS was measured by using HPLC. After 8-day treatment, weight, colon length and disease activity index (DAI) were measured. Inflammatory cytokines and oxidant biomarkers were measured by ELISA kits. The levels of cytokines, and key molecules in NF-κB pathway, were measured by using Western Blot. The effects of main ingredients of PCSE on cytokines and NF-κB signaling pathway were explored by using intestinal cells of a mouse UC model. The normality criterion was evaluated using the Saphiro-Wilk test. The quantitative variables were compared using the paired Student’s-t test. Results: The main ingredients of PCSE were polydatin, resveratrol and emodin. Polydatin may be transformed into resveratrol in the intestine of the mice. PCSE prevented DSS-caused weight loss and colon length reduction, and improved histopathology of UC mice (P <0.05). PCSE treatment increased the serum levels of IL-10 and reduced the levels of IL-1 beta，IL-6 and TNF-α (P < 0.05). PCSE increased the activities of SOD, CAT, GPX and reduced the level of MDA, BCL-2, beta-arrestin, NF-κB p65 and the activity of MPO (P<0.05). The combination of polydatin, resveratrol or emodin, and PCSE exhibited higher inhibitory activities for cytokines and NF-κB signaling related molecules than any one of the three ingredients with same concentration treatment. Conclusions: Oral administration of PCSE suppressed NF-κB signaling pathway and exerts its anti-colitis effects via possible synergistic effects of its main components.